A peptide hydrogel derived from a fragment of human cardiac troponin C. Issue 21 (19th February 2016) - De Leon-Rodriguez, Luis M.; Kamalov, Meder; Hemar, Yacine; Mitra, Alok K.; Castelletto, Valeria; Hermida-Merino, Daniel; Hamley, Ian W.; Brimble, Margaret A.
Abstract : The human cardiac troponin C peptide fragment H-V 9 EQLTEEQKNEFKAAFDIFVLGA 31 -OH self assembles into β-sheets fibrils that further entangle to give a hydrogels. Abstract : The human cardiac troponin C peptide fragment H-V 9 EQLTEEQKNEFKAAFDIFVLGA 31 -OH, which covers helix-A in the native protein, self-assembles into β-sheet fibrils in solution. These fibrils further entangle to give a hydrogel. This peptide may therefore serve as a template for development of novel biomaterials.